KESIAPAN MAHASISWA DALAM MENGHADAPI ASEAN ECONOMIC COMMUNITY 2015 (PERSEPSI MAHASISWA FAKULTAS EKONOMI, UNIVERSITAS INDONESIA) - Sugiharti, Harpa (Jurnal Riset Akuntansi dan Keuangan, 2014)
ASEAN Economic Community (AEC) in 2015 is one ofthe pillars whichis used as a tool in the achievement ofthe goal of ASEAN in the ASEAN Vision 2020.The objective of this study was to determine student treadinessin the face of employment in Indonesia when the AEC has been applied. This research is a descriptive qualitative research. Primary research data obtained by distributing questionnaires to students Faculty of Economic, University of Indonesia. The results showed that most of the students know how the impact of the implementation of the AEC and they have started to prepare for the competition.